(untitled) (American Journal of Research in Humanities and Social Sciences, 2026)
This article examines the theoretical and methodological foundations for organizing tutoring activities in distance and blended forms of professional development for prosecutorial staff. Within the framework of the study, the content, functions, rights, and responsibilities of tutoring activities in a digital educational environment, as well as their distinctive features compared to traditional teaching activities, were comparatively analyzed.